Don't Care High - Korman, Gordon (New York Scholastic, 1985)
Paul's attempts to adjust to New York City life are thwarted at his high school, nicknamed Don't Care High, until his manipulation of a new Student Council president wakes up the apathetic student body.
Keywords: High schools -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction